What Do Tourism Students Think about the Video Project? - Ira Mutiaraningrum; Sri Wuli Fitriati; Issy Yuliasri; Mursid Saleh (International Conference on Science, Education, and Technology, 2023)
This paper endeavors to examine perspectives on project-based learning implemented through making promotional videos among Indonesian vocational college students. Using a descriptive study, this research taps further into the applications/software the students used to finish their project in the English course. Involving 33 students from Tourism Business Management Study Program, this study used an open-ended survey to collect the data. Reflecting upon the findings, it was found that the students think that making promotional videos as part of project-based learning in their English course promotes creativity, productivity, communication skills, confidence, digital literacy skills, media literacy skills, learning autonomy, and employability skills. This study highlights the importance of promotional video-making activities for vocational college students that will lead to employability skills, which will be useful for students’ future careers.